Teaching tolerance through intercultural English language learning to elementary students - Fauzi Miftakh; Kelik Wachyudi (ELT in Focus, 2019)
This study aims to find out how the intercultural English language learning can foster values of tolerance in elementary school students, as well as how it is implemented by teacher in the classroom. This research used a case study research design and the subjects in this study were a teacher and 20 6th grade students at an elementary school in Karawang. Data collection techniques were carried out by observation in 4 class meetings to observe the learning activities and interview with a teacher and 6 students. From the observations, this study showed that intercultural English language learning was moderately relevant to apply to elementary students. The teacher used simple, fun and stimulating activities and material such as songs, short stories and games in English, both from native culture (Indonesian) and target culture (English). Students could learn the use of English while recognizing cultural differences between native and target culture and languages. On the other hand, from the interview, students stated that they were very pleased with the method applied. They expressed their pleasure because they could get to know other cultures and most importantly they accept cultural differences as an amazement. Therefore, it can be concluded that students at a young age are fair enough to be introduced intercultural learning so they can think critically and have a tolerant attitude from an early age. However, the teaching method and material should be adapted to their age and thinking capacity.